Offre globale en économie ouverte, courbe de Phillips et détermination du taux de chômage naturel : une reformulation théorique - Phaneuf, Louis (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
Criticizing the fact the Phillips curve wage and price equations are usually reduced form or quasi-reduced form equations without an explicit structural model behind, this article is an attempt to provide a supply side based structural model of the Phillips curve. Of special importance are the theoretical specifications of the resulting wage and price equations that include several new explanatory variables and especially policy variables. After having demonstrated under what structural conditions the price-Phillips curve of this model will be a vertical in the long run, the model is solved for the theoretical specification of the natural rate of unemployment.